Measuring health-related quality of life of care home residents: comparison of self-report with staff proxy responses. (7th January 2019) - Usman, Adeela; Lewis, Sarah; Hinsliff-Smith, Kathryn; Long, Annabelle; Housley, Gemma; Jordan, Jake; Gage, Heather; Dening, Tom; Gladman, John R F; Gordon, Adam L
Abstract: Introduction: care home residents are often unable to complete health-related quality of life questionnaires for themselves because of prevalent cognitive impairment. This study compared care home resident and staff proxy responses for two measures, the EQ-5D-5L and HowRU. Methods: a prospective cohort study recruited residents ≥60 years across 24 care homes who were not receiving short stay, respite or terminal care. Resident and staff proxy EQ-5D-5L and HowRu responses were collected monthly for 3 months. Weighted kappa statistics and intra-class correlation coefficients (ICCs) adjusted for clustering at the care home level were used to measure agreement between resident and proxies for each time point. The effect of staff and resident baseline variables on agreement was considered using a multilevel mixed effect regression model. Results: 117, 109 and 104 matched pairs completed the questionnaires at 1, 2 and 3 months, respectively. When clustering was controlled for, agreement between resident and staff proxy EQ-5D-5L responses was fair for mobility (ICC: 0.29) and slight for all other domains (ICC ≤ 0.20). EQ-5D Index and Quality-Adjusted Life Year scores (proxy scores higher than residents) showed better agreement than EQ-5D-VAS (residents scores higher than proxy). HowRU showed only slight agreement (ICC ≤ 0.20) between residents and proxies. Staff and resident characteristics did not influence level of agreement for either index. Discussion: the levels of agreement for EQ-5D-5L and HowRU raise questions about their validity in this population.